Pendidikan dan Pelatihan Dasar untuk Membentuk Profesionalisme Dosen Pegawai Pemerintah dengan Perjanjian Kerja (PPPK) di Lingkungan Kemendikbudristek - Dwi, Dwi Junida; Marbun, Posmanto (Digulis: Jurnal Pengabdian Pada Masyarakat, 2024)
Basic education and training for Government Employee lecturers with Work Agreements (PPPK) are vital so that a PPPK lecturer understands the duties and functions of ASN within the Ministry of Education and Culture. For this reason, basic education and training for Government Servant Lecturers with Work Agreements (PPPK) is equipped with values and ethics based on the core value of ASN BerAKHLAK so that the professionalism of Government Employee Lecturers with Work Agreements (PPPK) can be formed.  This education and training was provided to PPPK Wave II lecturers (Classes 8 to 15) at the Education and Training Center (Pusdiklat) of the Ministry of Education and Culture. This basic education and training activity uses a hybrid offline and online method and uses the Learning Management System (LMS) belonging to the Employee Education and Training Center, namely PIJAR. The result of this education and training is the formation of PPPK lecturers who can carry out their duties and functions professionally as community servants.